A version of the Characteristic Basis Finite Element Method (CBFEM) by utilizing Physical Optics for large-scale electromagnetic problems - Ozgun, O.; Mittra, R.; Kuzuoglu, M. (2009 IEEE Antennas and Propagation Society International Symposium, 2009)
In this paper, we present another version of the CBFEM (called CBFEM-PO), which is based on the use of physical optics (PO) and perfectly matched layers (PMLs) for the generation of the CBF. The CBFEM-PO constructs three types of CBFs, namely: (i) primary bases arising from the self-interactions in each subdomain; (ii) secondary bases due to the mutual couplings between subdomains; and (iii) bases that are derived from the PO fields for different incident angles, polarization and frequency. Below we present some representative examples to demonstrate the performance of the method in 3D electromagnetic scattering problems.